Implementation of Information and Communication Technology (ICT)-Based Learning in Pandemi and Post Pandemi Era in Madrasah Ibtidaiyah: Implementasi Pembelajaran Berbasis Teknologi Informasi dan Komunikasi (TIK) Era Pandemi dan Pasca Pandemi Di Madrasah Ibtidaiyah - Mamkua, Mamkua (Universitas Muhammadiyah Sidoarjo, 2023)
Information and communication technology-based learning is an effort to manage learning by utilizing ICT advances to support online-based learning processes, which combine a learning process with the use of learning media. The media is technological in nature, be it in the form of the internet, mobile phones, use of video, LCD, and others. The purpose of this research is to reveal the implementation of Information and Communication Technology (ICT)-based learning in the era of the Covid 19 pandemic and after the Covid 19 pandemic. This type of research uses a qualitative approach with a descriptive method. The technique of collecting data from this research is through interviews, opinions of experts and previous research. This research was conducted at an Islamic elementary school in Palembang city in January 2023. The results of this study indicate that during the Covid 19 pandemic the process of teaching and learning activities was carried out online using WhatsApp Groups, Google Classroom and Zoom Meetings. During the post-Covid 19 pandemic, learning was carried out face-to-face, but ICT-based learning was still carried out as it should and in the best way possible. The goal is to make it easier for teachers to convey material to students and also make it easier for students to accept the material being taugh.